Hiding in plain sight: eating disorders in diverse populations - a case for comprehensive medical education - Tashalee R. Brown; Madeline O. Jansen; Drew Hirsch; Habiba Amir; Alexis E. Duncan; Ginger E. Nicol (Journal of Eating Disorders)
Abstract Background Training gaps regarding the diagnosis and management of eating disorders in diverse populations, including racial, ethnic, sexual, and gender minoritized groups, have not been thoroughly examined. Objective This study aimed to examine resident physicians’ knowledge and attitudes regarding eating disorders in diverse populations, with a focus on areas for improved training and intervention. Methods Ninety-two resident physicians in internal medicine, emergency medicine, obstetrics/gynecology, psychiatry, and surgery at an academic center completed an online survey from 12/1/2020–3/1/2021, which comprised multiple choice and vignette-style open-ended questions to assess knowledge and attitudes toward the management and clinical presentations of eating disorders. Overall, the survey response rate was 25.7%. Descriptive statistics were reported. Vignette-style questions were analyzed using inductive coding and the frequency of responses was reported. Results A minority of resident physicians self-reported confidence in their knowledge of the medical complications (n = 42, 45%), risk factors (n = 38, 41%), and clinical presentations (n = 32, 35%) associated with eating disorders. Responses to vignette-style questions correctly identified relevant management methods (such as electrolyte monitoring and referral to specialty care), but demonstrated limited knowledge of the clinical presentation of eating disorders. Furthermore, most respondents reported a lack of knowledge regarding eating disorders in sexual and gender minoritized patients (n = 68, 73.9%) as well as racial and ethnic minoritized patients (n = 64, 69.6%). Conclusions Our findings suggest concerning gaps in knowledge and confidence among resident physicians with regard to the diagnosis and treatment of eating disorders, particularly in racial, ethnic, sexual, and gender minoritized patients. Moreover, responses to vignette-like questions indicate significant homogeneity in respondents’ perceptions of the clinical presentation of eating disorders, reflecting cultural biases which associate eating disorders with underweight, young, female patients. The majority did not feel competent in treating eating disorders in diverse populations and expressed desire for additional training in this area. More research is needed to better understand and address these gaps in eating disorder training, with the goal of increasing equity in patient outcomes.